Taj Mahal : autobiography of a bluesman / Taj Mahal with Stephen Foehr. - Mahal, Taj (Sanctuary, 2001)
Taj Mahal's musical career spans more than 35 years. He has released 36 albums, and has toured and recorded with Eric Clapton, Bonnie Raitt, John Lee Hooker, Miles Davis, Bob Marley and the Rolling Stones.